Pengantar ilmu hukum. Suatu pengenalan pertama ruang lingkup berlakunya ilmu hukum I - KUSUMAATMADJA, Mochtar (Alumni, 2000)
Pengantar ilmu hukum. Suatu pengenalan pertama ruang lingkup berlakunya ilmu hu...